Neuromuscular functioning of athletes and non-athletes in the drop jump - Viitasalo, J. T.; Sal, A.; Lahtinen, J. (European Journal of Applied Physiology, 1998)
This study compared neuromuscular functioning of the lower extremity muscles together with some kinetic and kinematic parameters before and during ground contact in drop jumps from two heights [0.4 m (DJ40) and 0.8 m (DJ80)] in 7 highly trained triple-jumpers and 11 physically active controls.The triple jumpers and control subjects differed with respect to their neuromuscular functioning in the drop jump exercise and they responded in a different way to the increase in dropping height.